MARKET TIMING, SELEKTIVITAS SAHAM SERTA KINERJA DARI PRODUK REKSA DANA SAHAM DI INDONESIA - Benny Kurniawan; Hermanto Siregar; Trias Andati (School of Business, Bogor Agricultural University (SB-IPB), 2016)
Mutual fund share is one of the attractive instruments in investment. This product is able to offer high returns with lower risk than investing directly into equities. However, the results found in the period of 2009-2014 were not the case. The return generated by equity funds was smaller than that of JCI. Because of this, the research on mutual funds was performed to measure the actual capability of mutual fund shares in Indonesia. This study used daily data of 44 stock mutual fund products in Indonesia. In this study, (1) Adjustment risk-return performance, (2) Selectivity of shares and, (3) Market timing were measured; furthermore, in market timing, the data were processed by the econometric models to determine the error model so that an appropriate regression model (OLS or ARCH / GARCH) could be selected. The result revealed that the ability of mutual fund shares in Indonesia is very low. Although the risk-return adjustment performance shown only produced one underperformed product, the selectivity stock is very low in which only 22% showed a positive result in Fama testing; in addition, the portfolio showed a similar composition. For market timing, only about 30% of products are able to apply it appropriately. From these results, it can be concluded that the capability of equity funds in Indonesia in the period of 2009-2014 was still low, both on the selectivity stocks and market timing.Keywords: econometrics, performance, market timing, stock mutual funds, stock selectivity